A critical study on impact damage simulation of IM7/8552 composite laminate plate. (May 2019) - Cui, Hao; Thomson, Daniel; Eskandari, Sina; Petrinic, Nik
Highlight: A critical evaluation of current dynamic modelling capability has been conducted. The performance of dynamic failure models was benchmarked against plate impact experiments. Future work for improving the performance of dynamic simulation has been suggested. The mechanical response of a typical composite material at different loading rate was reviewed. Abstract: Plate impact tests on IM7/8552 composite laminates with different projectile incident angles and velocities were carried out. Numerical simulations were conducted to predict the impact damage, with both Puck and LaRC failure criteria having been employed in this study. The dynamic failure performance of IM7/8552 lamina was reviewed first, by referring to data obtained from experiments conducted at a range of strain rates. The performance of the assessed modelling approaches was evaluated by comparing the results of simulations against experimentally (quantitatively and qualitatively) acquired projectile velocity, impact load and the failure modes of the plates. It proved to be challenging to model the macroscopic damage of the laminate at elevated projectile velocities; further improvement can be made through enriching the dynamic material data and mitigating the mismatch between the complex fibre architecture and its numerical representation.